Interleukin‐6 promotes skeletal muscle catabolism by activating tryptophan–indoleamine 2, 3‐dioxygenase 1–kynurenine pathway during intra‐abdominal sepsis. Issue 2 (7th March 2023) - Xie, Tingbin; Lv, Tengfei; Zhang, Tenghui; Feng, Dengyu; Zhu, Feng; Xu, Yi; Zhang, Liang; Gu, Lili; Guo, Zhen; Ding, Chao; Gong, Jianfeng
Abstract: Background: Inflammatory cytokine interleukin‐6 (IL‐6) plays a pivotal role in skeletal muscle degradation after intra‐abdominal sepsis (IAS), with mechanism remained to be elucidated. Indoleamine 2, 3‐dioxygenase 1 (IDO‐1), a key enzyme in converting tryptophan into kynurenine, could be activated by IL‐6, and kynurenine has been shown to be involved in muscle degradation. We hypothesized that IL‐6 could promote muscle degradation via tryptophan–IDO‐1–kynurenine pathway in IAS patients. Methods: Serum and rectus abdominis (RA) were obtained from IAS or non‐IAS patients. Mouse model of IAS‐induced muscle wasting was generated by caecal ligation and puncture (CLP) and lipopolysaccharide (LPS) injection. IL‐6 signalling was blocked by anti‐mouse IL‐6 antibody (IL‐6‐AB), and the IDO‐1 pathway was blocked by navoximod. To elucidate the role of kynurenine in muscle mass and physiology, kynurenine was administered to IAS mice treated with IL‐6‐AB. Results: Compared to non‐IAS patients, kynurenine levels in serum (+2.30‐fold vs. non‐IAS, P < 0.001) and RA (+3.11‐fold vs. non‐IAS, P < 0.001) were elevated, whereas tryptophan levels in serum (−53.65% vs. non‐IAS, P < 0.01) and RA (−61.39% vs. non‐IAS, P < 0.01) were decreased. Serum IL‐6 level of the IAS group was significantly higher compared to non‐IAS patients (+5.82‐fold vs. non‐IAS, P = 0.01), and muscle cross‐sectional area (MCSA) was markedly reduced compared to non‐IAS patients (−27.73% vs. non‐IAS, P < 0.01). In animal experiments, IDO‐1 expression was up‐regulated in the small intestine, colon and blood for CLP or LPS‐treated mice, and there was correlation ( R 2 = 0.66, P < 0.01) between serum and muscle kynurenine concentrations. Navoximod significantly mitigated IAS‐induced skeletal muscle loss according to MCSA analysis (+22.94% vs. CLP, P < 0.05; +23.71% vs. LPS, P < 0.01) and increased the phosphorylated AKT (+2.15‐fold vs. CLP, P < 0.01; +3.44‐fold vs. LPS, P < 0.01) and myosin heavy chain (+3.64‐fold vs. CLP, P < 0.01; +2.13‐fold vs. LPS, P < 0.01) protein expression in myocytes. In the presence of anti‐IL‐6 antibody, a significantly decreased IDO‐1 expression was observed in the small intestine, colon and blood in CLP or LPS mice (all P < 0.01), whereas the decrease of MCSA was alleviated (+37.43% vs. CLP + IgG, P < 0.001; +30.72% vs. LPS + IgG, P < 0.001). In contrast, additional supplementation of kynurenine decreased the MCSA in septic mice treated with IL‐6‐AB (both P < 0.01). Conclusions: This study provided novel insights into the tryptophan–IDO‐1–kynurenine‐dependent mechanisms that underlie inflammatory cytokine‐induced skeletal muscle catabolism during intra‐abdominal sepsis.